Effect of enhancers on permeation kinetics of captopril for transdermal system - Desai, B G; Annamalai, A R; Divya, B; Dinesh, B M (Asian Journal of Pharmaceutics (AJP), 2014)
Transdermal drug delivery system has seen a veritable explosion in the past decades. In the present scenario, very few transdermal patches are commercially available. The captopril being an antihypertensive drug requires chronic administration. Since the drug has an extensive first-pass metabolism, an attempt was made to develop transdermal drug delivery system for better patient compliance. In this study, flux and permeation enhancement trials of captopril were carried out using modified Franz diffusion cells through siloxane membrane for 8 h. Citral and dimethyl formamide as permeation enhancers showed the best permeability as compared to sodium tauroglycholate, sodium lauryl sulfate, etc. One longstanding approach for improving transdermal drug delivery uses penetration enhancers (also called sorption promoters or accelerants), which penetrate into skin to reversibly decrease the barrier resistance.